Standardization of Recipes for Tamarind Paste and Squash - Archana Pattar (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2013)
An attempt was made to use tamarind pulp for preparation of paste and squash. Changes in the chemical constituents during storage at ambient temperature were studied. Results showed that in the stored products, TSS, titratable acidity and sugar content increased, whereas, the amount of ascorbic acid decreased. Better quality of paste was prepared from 100g paste + 20g salt with 10ml oil + 20mg BHA, followed by 100g paste + 15g salt with 10ml oil + 20mg BHA. Squash with 30% juice, 50% TSS, 1% acidity and 0.5% salt was superior to the other recipes. Both tamarind paste and squash retained their characteristic colour, aroma, taste and were microbiologically safe up to 3 months of storage at room temperature.